Conjoint Community Resiliency Assessment Measure‐28/10 Items (CCRAM28 and CCRAM10): A Self‐report Tool for Assessing Community Resilience. Issue 3 (4th October 2013) - Leykin, Dmitry; Lahad, Mooli; Cohen, Odeya; Goldberg, Avishay; Aharonson-Daniel, Limor
Abstract: Community resilience is used to describe a community's ability to deal with crises or disruptions. The Conjoint Community Resiliency Assessment Measure (CCRAM) was developed in order to attain an integrated, multidimensional instrument for the measurement of community resiliency. The tool was developed using an inductive, exploratory, sequential mixed methods design. The objective of the present study was to portray and evaluate the CCRAM's psychometric features. A large community sample (N = 1, 052) were assessed by the CCRAM tool, and the data was subjected to exploratory and confirmatory factor analysis. A Five factor model (21 items) was obtained, explaining 67.67 % of the variance. This scale was later reduced to 10‐item brief instrument. Both scales showed good internal consistency coefficients (α = .92 and α = .85 respectively), and acceptable fit indices to the data. Seven additional items correspond to information requested by leaders, forming the CCRAM28. The CCRAM has been shown to be an acceptable practical tool for assessing community resilience. Both internal and external validity have been demonstrated, as all factors obtained in the factor analytical process, were tightly linked to previous literature on community resilience. The CCRAM facilitates the estimation of an overall community resiliency score but furthermore, it detects the strength of five important constructs of community function following disaster: Leadership, Collective Efficacy, Preparedness, Place Attachment and Social Trust. Consequently, the CCRAM can serve as an aid for community leaders to assess, monitor, and focus actions to enhance and restore community resilience for crisis situations.